Aerobic capacity is correlated with the ranking of boxers - Bruzas, V.; Stasiulis, A.; Cepulenas, A.; Mockus, P.; Statkeviciene, B.; Subacius, V. (Perceptual and Motor Skills, 2014)
The goal was to assess the aerobic capacity of boxers and its relation with sport mastery. Participants were 12 boxers from the Lithuanian national team (VO2max - 58.03 ± 3.00 ml/kg/min) of different weight classes. Their sport mastery ranking was established according to their achieved results during the last years of participation in amateur boxing contests. In a graduated treadmill running test, the boxers' aerobic capacity indices were established. Running speed at first and second ventilatory thresholds, VO2max, and maximal oxygen pulse had moderate to strong correlations with the boxers' sport mastery ranking. Aerobic capacity is an important fitness component of boxers in all weight categories. Special attention should be paid to development of cardiac capacity in the boxers' training processes, as with aerobic power and anaerobic threshold training.